Pengaruh Ekstrak Tauge terhadap Perkecambahan Benih Padi (Oryza Sativa L.) yang Lewat Masa Simpan - Mega Rosalita Ekaputri Koni; Jusna Ahmad; Devi Bunga Pagalla; Novri Youla Kandowangko; Magfirahtul Jannah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
The decline in seed quality due to storage beyond the shelf life is a major problem in rice cultivation. One effort that can be made to improve seed viability is through invigoration techniques using natural ingredients, such as bean sprout extract (Phaseolus radiatus), which contains growth hormones. This study aims to analyze the effect of bean sprout extract on the viability of Ciherang rice seeds that have exceeded their shelf life and to determine the best treatment. The study was conducted from August to November 2024 at the Biology Laboratory of the UPTD Seed Center, Supervision and Certification of Agricultural Seeds of Gorontalo Province. The study used a two-factor Randomized Block Design (RBD) with bean sprout age (3, 5, and 7 days after sowing) and bean sprout extract concentration (20 g/L, 40 g/L, and 60 g/L) as factors, with four replications. The parameters observed included germination rate, maximum growth potential, and sprout length. The data were analyzed using ANOVA and DMRT post-hoc test at a 5% level. The results showed that bean sprout extract had a significant effect on all observed parameters. The treatment of 5-day-old bean sprouts with a concentration of 20 g/L gave the best results with a germination rate of 95.5%, maximum growth potential of 98.5%, and the highest sprout length. Sprout extract has the potential to be used as a natural alternative to improve the quality of rice seeds that have passed their storage period.